Dukungan Sosial dan Kebahagiaan Subjektif Remaja Buddhis: Sebuah Kajian Literatur Sistematis - Partono Nyanasuryanadi; Putri Setiyani (Jurnal Ilmiah Literasi Indonesia, 2026)
This study aims to examine the relationship between social support and subjective well-being in Buddhist adolescents and young adults using a Systematic Literature Review (SLR) approach. Fifty relevant scientific articles were systematically analyzed to identify patterns of empirical findings, methodological variations, and levels of cultural sensitivity in measurement. The results indicate that social support, particularly from family, peers, and the religious community (sangha), is consistently positively related to subjective well-being. However, most studies are still dominated by quantitative, cross-sectional designs and the use of Western instruments that are less sensitive to the values ​​and meanings of happiness in Buddhist culture. Measurement of subjective well-being primarily emphasizes cognitive and affective aspects, while the eudaimonic and spiritual dimensions receive relatively little attention. The limitations of longitudinal, qualitative, and mixed-methods approaches also limit our understanding of the temporal and contextual dynamics of well-being. Therefore, future research is recommended to develop culture-based instruments and employ more diverse methodological designs to produce more comprehensive and culturally relevant findings.